Use of pectin in patients with diabetes mellitus type 2 in the complex treatment of the periodontal disease (report 2) - Kosenko, S. V.; Balaban, I. O.; Hayoshko, O. B.; Ilnytska, O. M.; Yatsynovych, N. M.; Ivanov, S. O.; Muzichenko, N. I. (Zaporozhye Medical Journal, 2014)
Introduction. According the literature problem of the treatment of patients with periodontal tissues pathology, accompanied by diabetes mellitus, is serious and is not always successfully solved. Drugs that inhibit glucose absorption (polysugars) are effective in diabetes mellitus. "Pektodent" (Ukraine) applying in the treatment and prevention of chronic generalized periodontitis of II-III degree in patients with diabetes mellitus type 2 can be appropriate in this case. The objective of this study was to develop technologies to ensure long-term rehabilitation in patients with diabetes mellitus after treatment of periodontal tissues. Materials and methods. 45 patients with diabetes type 2 with chronic generalized periodontitis of II-III severity grade were under observation for 12 months. Patients were divided into two groups, control (n = 22) and primary (n = 23). Clinical, laboratory and X-ray methods were used. The results of the treatment process were evaluated on the 1st, 7th and 14th day of research. The results of the rehabilitation process were evaluated in 30 days after treatment, and after 3, 6, and 12-month studies. Feasibilities of rehabilitation technology were determined by assessment of the influence on diabetes type 2 pathogenesis, and chronic generalized periodontitis of II-III degree Results and discussion. Endo-and exogenous application of "Pektodent" as a hygienic and prophylactic drug for oral use can significantly prolong remission period and reduce aggressive course as periodontitis and diabetes, normalizing blood pressure. Conclusions. 1. Pektodent" application in the treatment of periodontal tissues may provide long-term rehabilitation in patients with diabetes. 2. Rehabilitation period indicators in patients with diabetes mellitus type 2, such as a capillary glucose level in blood plasma, blood pressure, and impressive appearance of the lactobacilli that decrease Candida in the mouth were signs of quality treatment of generalized periodontitis of II-III degree.